El Salvador : Technical Note on Safety Nets and Crisis Management Arrangements. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2014)
This Technical Note presents an assessment of safety nets and crisis management arrangements in El Salvador. In El Salvador, the bank safety net-emergency liquidity assistance, resolution, and deposit insurance-faces particular challenges given that it operates in the context of official dollarization. To address systemic liquidity risk in the context of official dollarization, the Banco Central de Reservas should be provided with more powers and funds to provide emergency liquidity assistance to banks. The bank resolution plan, which has not been tested, and the deposit insurance fund, which has insufficient funds, both need to be strengthened. The authorities should also consider making the necessary changes to the banking law to strengthen the resolution and depositor insurance frameworks, as well as issuing the necessary regulations and guidelines.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet